2006
DOI: 10.1191/0961203306lu2258cr
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumonia with antiphospholipid antibodies and a cardiac thrombus

Abstract: A case is reported of a four-year old child with mycoplasma pueumonia with a left atrial thrombus secondary to aPL antibodies. He was anticoagulated and the thrombus resolved in six months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…M. pneumoniae is a major cause of respiratory infections in school-aged children and young adults and also has been associated with the presence of aPL, particularly in patients with severe infection and in patients with high titer of cold hemagglutinins [40]. Recently, M. pneumoniae infection was reported in several pediatric cases with thrombotic events secondary to aPL, including cardiac thrombus, internal carotid artery occlusion, and two cases with splenic infarcts [41,42].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…M. pneumoniae is a major cause of respiratory infections in school-aged children and young adults and also has been associated with the presence of aPL, particularly in patients with severe infection and in patients with high titer of cold hemagglutinins [40]. Recently, M. pneumoniae infection was reported in several pediatric cases with thrombotic events secondary to aPL, including cardiac thrombus, internal carotid artery occlusion, and two cases with splenic infarcts [41,42].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…[8] During acute Q fever, IgG aCL are more frequent than lupus anticoagulant and IgM anticardiolipin antibodies, whereas anti-β2glycoprotein I antibodies are very rare. [3,9] However, “infectious” aCL, which are generally β2-glycoproetin I independent, were believed to be found in conditions not involving thrombotic complications, [7] whereas antiphospholipid-associated thrombosis during infections has been reported with Mycoplasma pneumoniae, [1013] Bacteroides, [14] EBV, [15] CMV, [16,17] HIV, [18,19] HBV, [20] and HCV. [21] …”
Section: Introductionmentioning
confidence: 99%
“…There are five previous reports in the literature of M. pneumoniae infection in children associated with thromboembolic episodes, one of these associated with a familial antithrombin deficiency. [2][3][4][5][6] A recent Swedish study of 128 children admitted with a first episode of venous thromboembolism showed 54% to have a combination of risk factors for venous thrombosis. 7 The presence of acquired activated protein C resistance with anti-phospholipid antibodies has been reported previously, and is attributed to B2-glycoprotein 1 and anti-prothrombin antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…There are five previous case reports associating infection with M. pneumoniae with the development of thromboembolism. [2][3][4][5][6] The mechanism by which Mycoplasma infections can cause thrombosis may be multifactorial, including the development of autoantibodies.…”
Section: Introductionmentioning
confidence: 99%